The The Effect of Potential Water Pressure on the Emergence of Radicles in Maize Seeds (Zea mays): Pengaruh Tekanan Potensial Air Terhadap Kemunculan Radikula pada Benih Jagung (Zea mays) - Suwarno, Punjung Medaraji Suwarno; Abdul Qadir; Aditya Kusumawardana; Ritawati (IPB University, 2023)
Water is an important factor for plant growth. A few studies about the amount of water required by the seed for radicle emergence in germination has been done. This research was conducted at the Laboratory of Seed Science and Technology, Faculty of Agriculture IPB Bogor. Maize seeds were planted using a solution of Polyethylene Glycol (PEG) 6000 with a concentration level of 0%, 5%, 10%, 20%, and 30%. A Completely Randomized Design with 3 replications was used in this research. The appearance of the radicle first occurred in phase II, namely during the 48-hour observation for the Ψ -0,13 MPa treatment (5% PEG) and 60 hours for the Ψ -0,4 MPa treatment (10% PEG). The results showed that testing maize seed vigor under drought stress can use water potential (Ψ) higher than -0,4 MPa. The results showed that water potential (Ψ) of -0,4 MPa or higher can be used in vigor testing of maize seed.